Mediating role of inclusive leadership in innovative teaching behavior - Cardoza Sernaqué, Manuel Antonio (2022)
Purpose: The prime purpose of current research is to investigate the mediating role of inclusive leadership between teaching policy, teachingresources,and innovativeteaching behavior. Design/methodology/approach: This research has collected data on a Likert scale questionnaire and the structural equation modeling technique is applied in data analysis.The population of this research are teachers in Peru. Findings: The findings of this research highlighted that the mediating role of inclusive leadership is significant between teaching policy, teachingresources,and innovative teaching behavior.Furthermore, the research highlighted that the direct impact of teaching policy, teachingresources, and inclusiveleadership are significant in innovative teaching behavior.Research limitations/implications: This research has theoretical implications as it has enhanced the model of innovative teaching with mediating role of inclusive leadership. Furthermore, the practical implications of this research can improve teaching behavior innovatively by adopting new policies for teaching and utilizing appropriate resources for it. Originality/value: This research is designed on the original idea to improve the model of innovative teaching behavior with inclusive leadership to provide remarkable implications in the knowledge and practice.